2002
DOI: 10.1242/jcs.00065
|View full text |Cite
|
Sign up to set email alerts
|

The growth ofDrosophilabristles and laterals is not restricted to the tip or base

Abstract: The highly elongated bristles of Drosophila have proven to be a valuable model system for studying cellular morphogenesis. Extending bristles contain a series of large bundles of actin filaments juxtaposed to the plasma membrane and centrally located microtubules. Models to explain the extension of the bristle have principally focused on the assembly of actin filaments at the distal tip of the bristle. We have used time-lapse observations of wild-type and mutant bristles and the related arista laterals and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…Whereas actin assembly is crucial for bristle cell elongation, MTs must provide other functions, such as providing bulk to the bristle cytoplasm, as well as playing a role in vesicle transport. It has also been shown that MT antagonists such as vinblastine and colchicine resulted in a decreased axial length and a compensatory increase in width, so that the volume of the bristle was not significantly changed (Fei et al, 2002). These data suggest that the MT cytoskeleton is of central importance for growth to be polarized in the axial direction (Fei et al, 2002).…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Whereas actin assembly is crucial for bristle cell elongation, MTs must provide other functions, such as providing bulk to the bristle cytoplasm, as well as playing a role in vesicle transport. It has also been shown that MT antagonists such as vinblastine and colchicine resulted in a decreased axial length and a compensatory increase in width, so that the volume of the bristle was not significantly changed (Fei et al, 2002). These data suggest that the MT cytoskeleton is of central importance for growth to be polarized in the axial direction (Fei et al, 2002).…”
Section: Research Articlementioning
confidence: 99%
“…It has also been shown that MT antagonists such as vinblastine and colchicine resulted in a decreased axial length and a compensatory increase in width, so that the volume of the bristle was not significantly changed (Fei et al, 2002). These data suggest that the MT cytoskeleton is of central importance for growth to be polarized in the axial direction (Fei et al, 2002). Mutations in the Dynein heavy chain resulted in shorter and thicker bristles (Gepner et al, 1996); mutations in kinesin also resulted in shorter and thicker bristles, and the tips of bristles were often contorted, exhibiting flattened, flared or twisted tips (Brendza et al, 2000).…”
Section: Research Articlementioning
confidence: 99%
“…Studies of cytoskeletal regulation in the larger adult sensory bristles may guide this. EM studies, the use of cytoskeletal inhibitors, and FRAP, which proved informative in studies of wing hairs and bristles (Fei et al, 2002;Tilney et al, 1995;Tilney et al, 1996;Tilney et al, 2000a;Turner and Adler, 1998), may reveal how actin in denticles is assembled. Finally, it will be important to study in denticles additional actin regulators that regulate bristle development (Hopmann and Miller, 2003;Wahlstrom et al, 2001).…”
Section: Journal Of Cell Science 119 (3)mentioning
confidence: 99%
“…Polarized extensions of epidermal cells, such as the sensory bristles, arista laterals and wing hairs of Drosophila melanogaster, are good model cell types for studying the processes that govern cytoskeleton-mediated morphogenesis (Fei et al, 2002;Guild et al, 2005;Tilney et al, 2004;Tilney et al, 1995;Tilney and DeRosier, 2005;Turner and Adler, 1998). However, little is known about the mechanisms that mediate membrane and protein transport during the growth of these structures.…”
Section: Introductionmentioning
confidence: 99%
“…Time-lapse studies have shown that, except for the initial stages of bristle development when growth is primarily isotropic, bristle growth is highly polarized in the axial direction (Fei et al, 2002). A variety of genetic and inhibitor studies argue that actin and microtubules play different roles in bristle growth (Cant et al, 1994;Fei et al, 2002;He and Adler, 2001;Petersen et al, 1994;Tilney et al, 2000a;Turner and Adler, 1998).…”
Section: Introductionmentioning
confidence: 99%